Comparison of Microalgae Cultivation in Photobioreactor, Open Raceway Pond, and a Two-Stage Hybrid System - Narala, Rakesh R.; Garg, Sourabh; Sharma, Kalpesh K.; Thomas-Hall, Skye R.; Deme, Miklos; Li, Yan; Schenk, Peer M. (Frontiers in Energy Research, 2016)
In the wake of intensive fossil fuel usage and CO2 accumulation in the environment, research is targeted towards sustainable alternate bioenergy that can suffice the growing need for fuel and also that leaves a minimal carbon footprint. Oil production from microalgae can potentially be carried out more efficiently, leaving a smaller footprint and without competing for arable land or biodiverse landscapes. However, current algae cultivation systems and lipid induction processes must be significantly improved and are threatened by contamination with other algae or algal grazers. To address this issue, we have developed an efficient two-stage cultivation system using the marine microalga Tetraselmis sp. M8. This hybrid system combines exponential biomass production in positive pressure air lift-driven bioreactors with a separate synchronized high-lipid induction phase in nutrient deplete open raceway ponds. A comparison to either bioreactor or open raceway pond cultivation system suggests that this process potentially leads to significantly higher productivity of algal lipids. Nutrients are only added to the closed bioreactors while open raceway ponds have turnovers of only a few days, thus reducing the issue of microalgal grazers.